Accuracy of Diagnostic Biopsy for Cutaneous Melanoma: Implications for Surgical Oncologists. (11th September 2013) - Hieken, Tina J.; Hernández-Irizarry, Roberto; Boll, Julia M.; Jones Coleman, Jamie E.
Abstract : Background and Objectives . While excisional biopsy is recommended to diagnose cutaneous melanoma, various biopsy techniques are used in practice. We undertook this study to identify how frequently final tumor stage and treatment recommendations changed from diagnostic biopsy to final histopathology after wide local excision (WLE). Methods . We compared the histopathology of the dermatopathologist-reviewed diagnostic biopsy and final WLE in 332 cutaneous melanoma patients. Results . Tumor sites were extremity (51%), trunk (33%), and head/neck (16%). Initial biopsy types were excisional (56%), punch (21%), shave (18%), and incisional (5%). Most diagnostic biopsies were margin positive regardless of technique, and 36% of patients had residual melanoma on WLE. T-stage changed in 8% of patients, of whom 59% were diagnosed by punch biopsy, 15% by incisional biopsy, 15% by shave biopsy, and 11% by excisional biopsy (P < 0.0001 ). Treatment recommendations changed in 6%: 2% after excisional biopsy, 5% after shave biopsy, 18% after punch biopsy, and 18% after incisional biopsy (P < 0.0001 ). Conclusions . Although most biopsy margins were positive, T-stage and treatment changed for only a minority of melanoma patients. Our data provide valuable information to inform patient discussion regarding the likelihood of a change in prognosis and the need for secondary procedures after WLE. These data support the superiority of dermatopathologist-reviewed excisional biopsy when feasible.